Leveraging on training to enhance employee performance: a case study of Zimbabwe Revenue Authority - Sibanda, Fidelis (Midlands State University, 2017)
The research sought to determine the importance of training in enhancing the performance of employees. The research was driven by the need to demonstrate the value of training in fostering attainment of organisational goals through employees. Research was carried out at the Zimbabwe Revenue Authority (ZIMRA) Head Office. Research objectives were to establish the training process in the organisation, ascertain how transfer of training is facilitated, to determine how the effectiveness of training is measured and to assess employee perceptions towards training in the organisation. A sample of 36 participants including both managerial and non managerial employees took part in the study. The research utilized a Case study method and questionnaires and interviews were used to gather data from research participants. The instructional systsems design formed the theoretiocal basis of this research and this model emphasised that training should be systematic if it is to achieve its intended goals. Data was presented through the thematic method and was presented both qualitatively and quantitatively. From the research it was concluded that investing in training is a necessity that organisations can leverage on to improve employee performance. The researcher recommended the organisation to invest more in technology to facilitate effective transfer of training, decentralize training activities to station level and also develop systems that measure the impact of training rather than the training activity.